S’adapter au changement climatique sur le littoral : retours empiriques sur une démarche participative chercheurs-habitants (Côte d’Opale, France) - Anne-Peggy Hellequin; Caroline Rufin-Soler; Philippe Deboudt; Marie-Hélène Ruz; Florian Lebreton; Arnaud Héquette; Vincent Herbert (Territoire en Mouvement)
This article presents and provides an empirical feedback on a participatory action process of co-construction of climate change adaptation strategies between researchers and residents of two coastal municipalities in the Hauts-de-France region (Oye-Plage and Wissant). The article is structured in two parts. The first part presents the methodological protocols used with a description of the participatory mechanisms (public meetings, participatory workshops, collaborative monitoring) and the tools used by the researchers. The second part provides feedback on these mechanisms by highlighting three main results following the analysis of this participatory approach and by underlining its progress and limitations.